(untitled) (Olhar de Professor, 2021)
The article presents partial results of a collective work that articulates research and extension actions, adopting Culture Circles as a pedagogical, and epistemological principle in the educational field. In this sense, research and extension are assumed with concrete questions in a system whereby are constantly being improved by dialectical and dialogical method. The bibliographic study approached Paulo Freire’s Pedagogy of Liberation and Intercultural Transformation of Philosophy Program proposed by Raúl Fornet-Betancourt having as convergence between interculturality and dialogicity in the construction of “viable unpublished”. Aspects of these authors’ thoughts and some current initiatives are referred within the scope of this article. We conclude that it is possible to intervene in the instituted, to cause displacements in favour of a new ethos, and that Circles of Culture present themselves with epistemic, ethical and political potential. These actions contribute to the liberating intercultural practices as opposed to forms of brutalization of the other and reproducing colonized mentalities. Keywords: Intercultural Philosophy. Liberating Pedagogy. Culture Circles.